Assessment of the role of brassinosteroid in regulating the disease resistance of postharvest tomato fruit by proteomic analysis. Issue 9 (29th June 2021) - Ding, Yang; Sheng, Jiping; Cheng, Fansheng
Abstract: This study aimed to investigate the effects of brassinosteroid (BR) on disease development, disease resistance‐related enzyme activities, gene expression, and proteomic change in tomato ( Solanum lycopersicum ) fruits infected by Alternaria solani . The results showed that BR pretreatment inhibited disease development and increased the activities of disease resistance‐related enzymes. Fruits treated by brassinazole, the biosynthesis inhibitor of BR, are more sensitive to A . solani . BR could promote the gene expression of downstream and upstream in the systematic acquired resistance (SAR) pathways and the catalyzers in the biosynthetic pathways of phenolic and quinone compounds. The proteomic analysis showed that BR upregulated the expression of 2 proteins and downregulated the expression of 13 proteins. Furthermore, one upregulated protein was involved in the phenylpropanoid biosynthetic pathway. These results suggested that BR‐mediated disease resistance in tomato fruits could share some SAR downstream genes and phenylalanine ammonia‐lyase and also have distinct pathways. Practical applications: Brassinosteroid treatment before harvest could be a useful strategy to improve the quality of tomato fruit and reduce postharvest losses caused by fungi disease.